Three-dimensional Cat Virtual Anatomy: Development of an Interactive Virtual Anatomical Software - Osorio-Echeverri, Juan Sebastián; Orrego-Metaute, Diana Alexandra; Murillo-Escobar, Juan Pablo; Tamayo-Arango, Lynda (Journal of Morphological Sciences, 2019)
Background Three-dimensional (3D) virtual models are novel tools to teach veterinary anatomy.Objective The aim of the present study was to create a 3D cat image software and a library of cross-sectional images.Methods Modeling of the 3D cat organs and structures was done with Autodesk Maya, version 2017 (Autodesk Inc., San Rafael, California, USA) and ZBrush, version 4R7 (Pixologic, Los Angeles, CA, USA) software. In order to obtain the images for the library, three cadavers of adult cats were used, with the following techniques: 1) scanning by magnetic resonance imaging (MRI) at 3-mm intervals, 2) scanning by computed tomography (CT) at 2-mm intervals, and 3) photographing of 178 transverse cuts at 2.5-mm intervals from the frozen cadavers. Out of all the images, thirty images of each technique were selected. An interactive software was developed with the modeled 3D cat and the selected images using Unity, version 5.4 (Unity Technologies, San Francisco, CA, USA).Results A virtual 3D cat model was obtained with 418 labeled structures of the skeletal, muscular, circulatory, nervous, respiratory, digestive, urinary, and integumentary systems. The virtual interface enables the manipulation of the 3D cat in all views and the visualization of the selected images in a chosen localization along the body of the cat. The library of images allows comparison among CT, MRI and photographs of transverse cuts.Conclusions The software interface facilitates the access to the content for the user. Sectional images of the cat and of its body structures can be easily understood. This new 3D software of cat anatomy is another tool that can be used in teaching veterinary anatomy.
Keywords: three-dimensional anatomy; education in anatomy; multimedia anatomy resources